1987
DOI: 10.1536/ihj.28.143
|View full text |Cite
|
Sign up to set email alerts
|

The first heart sound in normal and pathological conditions.

Abstract: SUMMARYConsiderations of the physical basis of cardiac contraction and sound generation explain the mechanism of the first sound. Older theories examining this sound as the result of valve closure or stiffening are refuted.It has been demonstrated that the normal first sound originates in the left ventricle alone and that accelerations and decelerations, "timed" by mitral and aortic valves events, are its cause. Three components have been recognized in the first sound: a occurs when the left ventricular wall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…With RBBB the S1 tends to be widely spitted with a preserved amplitude and a larger late component. as shown in a previous study 7 , 8 . In this study, RBBB morphology PVC (LV origin) was characterized by increased S1 duration and complexity, which were compatible with previous findings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With RBBB the S1 tends to be widely spitted with a preserved amplitude and a larger late component. as shown in a previous study 7 , 8 . In this study, RBBB morphology PVC (LV origin) was characterized by increased S1 duration and complexity, which were compatible with previous findings.…”
Section: Discussionsupporting
confidence: 85%
“… 7 studied 20 right bundle branch block (RBBB) subjects and 67 normal subjects with simultaneous echocardiogram of valves, electrocardiogram, and phonocardiogram. Wide splitting of the S1 was observed in RBBB subjects 7 , 8 . These studies demonstrated the wavefront of ventricular myocardial activation affect the timing of valvular closure, which could be detected and quantified by well-designed acoustic cardiography device.…”
Section: Introductionmentioning
confidence: 92%
“…Multiple acoustic variables were found to be associated with LVEF. (i) E1, the acoustic correlate of the mitral component of the first heart sound that is related to LV contraction [6], was positively associated with LVEF. (ii) Diastolic acoustic signals (ED) were negatively associated with LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Also included was Aldo A. Luisada , a distinguished cardiologist from Ferrara who left Italy in 1939 to become a faculty member at the medical school of the University of Chicago. Luisada, founder and first president of the Laennec Society for Cardiovascular Sound, is remembered for his researches in phonocardiography to monitor cardiac performance and on the mechanisms of heart sound generation and cardiac contraction (40,41).…”
Section: Jews In Italy and In Medical Schoolsmentioning
confidence: 99%